Optimization And Existence Of The Role Of National Police Investigators In The Investigation And Investigation Of Corruption In Local Government Grant Spending : Research Study At The Riau Islands Police Directorate - Suhendri Atmoko; Dahlan Dahlan; Ramlan Ramlan; Erniyanti Erniyanti; Soerya Respationo (Badan Penerbit STIEPARI Press, 2024)
The crime of corruption in local government grant spending is a serious problem that has an impact on state losses and public trust in the government. This research focuses on optimizing and existing the role of National Police investigators in the investigation and investigation of corruption crimes at the Riau Islands Police Directorate of Criminal Investigation (Riau Islands). The background of this research is the importance of the role of the National Police in uncovering and eradicating corruption, as well as the challenges faced in its implementation. The purpose of this study is to identify the obstacles faced by National Police investigators and find optimal solutions to increase the effectiveness of investigations and investigations into corruption in local government grant spending. The research method used is a qualitative method with a case study approach. The data was obtained through in-depth interviews with investigators at the Riau Islands Police Directorate of Criminal Investigations, analysis of legal documents, and direct observation of the investigation and investigation process. Data analysis was carried out using triangulation techniques to ensure the validity and reliability of the findings. The results of the study show that National Police investigators face various obstacles, including limited human resources and technology, the complexity of corruption cases, political intervention, weaknesses in the internal supervision system, and a less supportive legal culture. The proposed solutions include increasing the capacity and competence of investigators through special training, procurement of advanced technology, increasing operational budgets, and strengthening cross-agency cooperation such as with the KPK and BPKP. In addition, adequate legal protection for investigators and reform of local government internal supervision are essential to ensure the independence and effectiveness of investigations. This study suggests that National Police investigators continue to improve their capacity and competence, the community actively participates in supervising the use of grant funds, and local governments strengthen the supervision and transparency system. With this holistic approach, it is hoped that the role of National Police investigators in eradicating corruption in local government grant spending can be optimized and its existence will be further strengthened.